2004
DOI: 10.1007/s00426-004-0188-3
|View full text |Cite
|
Sign up to set email alerts
|

Eye direction aftereffect

Abstract: Three experiments using computer-generated human figures showed that after a prolonged observation of eyes looking to the left (or right), eyes looking directly toward the viewer appeared directed to the right (or left). Observation of an arrow pointing left or right did not induce this aftereffect on the perceived eye direction. Happy faces produced the aftereffect more effectively than surprised faces, even though the image features of the eyes were identical for both the happy and the surprised faces. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 42 publications
5
51
1
Order By: Relevance
“…In this study, another person's gaze shift affected the appearance of motion stimuli. In addition to the previously used approaches of measuring reaction time for detecting static targets (e.g., Driver et al, 1999;Friesen & Kingstone, 1998;Langton & Bruce, 1999), or accuracy for discriminating static gaze direction (Ando, 2002;Jenkins, Beaver, & Calder, 2006;Ricciardelli, Baylis, & Driver, 2000;Seyama & Nagayama, 2006;Sinha, 2000;Todorović, 2006), our approach offers a new index for the assessment of the dynamic state of attention by measuring the modulation of perceived motion direction by the dynamic gaze shift. In Bavelier et al (2002), although the researchers demonstrated that another person's gaze shift induced motion perception against a static horizontal line, it differs from our experiment in that they used the static gaze direction to examine the effect of gaze cueing on motion perception.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, another person's gaze shift affected the appearance of motion stimuli. In addition to the previously used approaches of measuring reaction time for detecting static targets (e.g., Driver et al, 1999;Friesen & Kingstone, 1998;Langton & Bruce, 1999), or accuracy for discriminating static gaze direction (Ando, 2002;Jenkins, Beaver, & Calder, 2006;Ricciardelli, Baylis, & Driver, 2000;Seyama & Nagayama, 2006;Sinha, 2000;Todorović, 2006), our approach offers a new index for the assessment of the dynamic state of attention by measuring the modulation of perceived motion direction by the dynamic gaze shift. In Bavelier et al (2002), although the researchers demonstrated that another person's gaze shift induced motion perception against a static horizontal line, it differs from our experiment in that they used the static gaze direction to examine the effect of gaze cueing on motion perception.…”
Section: Discussionmentioning
confidence: 99%
“…eye direction after-effect [14]). Such responsiveness of gaze seems to affect what kind of impression is perceived by the partner.…”
Section: Introductionmentioning
confidence: 99%
“…For example, after looking at a picture of a male face, an androgynous face can appear feminine (Webster et al, 2004). Analogous effects occur between faces of different expressions (Hsu & Young, 2010), ethnicities (Webster et al, 2004), ages (Schweinberger et al, 2010), eye gaze directions (Jenkins, Beaver, & Calder, 2006;Seyama & Nagayama, 2006), head directions (Fang & He, 2005), and identities (Leopold et al, 2001).…”
Section: Adaptation To Faces and Other Complex Objectsmentioning
confidence: 99%
“…Aftereffects induced by the direction of eye gaze (Seyama & Nagayama, 2006) and head viewpoint (Fang & He, 2005), for instance, seem to be better accounted for by a multichannel coding scheme Calder et al, 2008;Lawson et al, 2011.…”
Section: Reasons To Question the Norm-based Opponent Coding Account Omentioning
confidence: 99%
See 1 more Smart Citation